Integrative Approaches to New Product Development and Sensory Optimization: A Comparative Analysis of Non-Traditional Flours and Fruit-Based Matrices in Functional Food Systems - Markus Faber (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
The contemporary food industry is undergoing a paradigm shift driven by consumer demand for health-promoting functional foods and the necessity for robust New Product Development (NPD) frameworks. This research article synthesizes two critical trajectories in food science: the optimization of sensory and chemical monitoring in fruit-based beverages, specifically pomegranate and apple juices, and the fortification of cereal-based products using water chestnut (Trapa natans) flour. By examining the efficacy of electronic tongues alongside traditional sensory panels, this study evaluates the reliability of instrumental measurements in predicting consumer preference. Furthermore, the article explores the rheological and nutritional implications of incorporating non-traditional tubers into bakery formulations. The methodology adheres to ISO standards for sensory analysis, ensuring a rigorous environment for hedonic testing. Results indicate that while instrumental tools provide high precision in detecting chemical variance, human sensory perception remains the ultimate arbiter of market success. The integration of market-oriented development models, such as the Stage-Gate process, is highlighted as essential for bridging the gap between laboratory innovation and consumer acceptance. This comprehensive analysis provides a theoretical and practical roadmap for food technologists aiming to balance nutritional fortification with palatability in a competitive global market.